Where is Philemon? The Case for a Logical Fallacy in the Correlation of the Data in Philemon and Colossians 1.1-2; 4.7-18. (December 2015) - Balabanski, Vicky
Based on the internal evidence of the letters to Philemon and to the Colossians (Col. 1.1-2; 4.7-18), this article contends that there have been logical errors in how we have correlated the data between the two letters. Arguing that the two letters were not written to be sent simultaneously, this article demonstrates that syllogistic fallacies have shaped scholarly assumptions, leading to the view that the overlapping data necessarily indicate that Philemon, Apphia and the church in Philemon's house were located in Colossae. Once the logical fallacies in correlating the data are recognized, the apparent problem of the lack of greeting to Philemon in Colossians is in fact no problem at all: Philemon and his house-church were located in Italy, possibly in Rome itself.